The Correlation of Treatment Adherence with Clinical Outcome and Quality of Life in Patients with Type 2 Diabetes - Syaiful Katadi; Tri Murti Andayani; Dwi Endarti (Faculty of Pharmacy, Universitas Gadjah Mada)
Patients with diabetes mellitus (DM) are patients with a low level of treatment adherence. Low adherence is often the cause of treatment failure, so the risk of complications is higher and can affect the quality of life of patients. This study aimed to determine the relationship between treatment adherence to clinical outcomes and the quality of life of patients with type 2 DM. This study used a cross sectional design involving patients with type 2 DM who met the inclusion and exclusion criteria in three health centers in Bantul, Yogyakarta. Data on patient medication compliance was obtained using medication adherence report scale questionnaire (MARS-5), patient quality of life data using Short-Form 6 Dimensions questionnaire (SF-6D), data on fasting blood glucose levels (GDS / GDP) from medical records, socio demographic data obtained from respondents and medical records. The relationship between the level of adherence to clinical outcomes using Chi-square analysis while the relationship between the level of adherence to quality of life using Spearman Rho analysis. The total number of respondents involved was 179 patients, the majority had a low level of adherence (57%), clinical outcomes that had not been achieved (68.7%), and the average utility score was high (0.816). There was a relationship between medication adherence to clinical outcomes (P = 0.002; OR = 2.875). Similarly, between adherence to quality of life, there is a significant relationship (P = 0.006) with a weak correlation level (r = 0.204). Therefore, patients and Health professionals, especially pharmacists, need to pay attention to medication adherence to achieve optimal clinical outcomes and a better quality of life.